2021
DOI: 10.33102/sainsinsani.vol6no2.312
|View full text |Cite
|
Sign up to set email alerts
|

Kebolehpasaran Siswazah Melalui Pendekatan Pembelajaran Berasaskan Kerja Di Politeknik

Abstract: Pembelajaran Berasaskan Kerja (PBK) merupakan suatu kaedah pembelajaran yang menggabungkan dua medium pembelajaran iaitu pembelajaran teori di institusi pendidikan dan pengaplikasian amali di industri. Melalui penggabungan dua medium pembelajaran ini dapat memberi pendedahan dan pengalaman industri yang relevan mengikut bidang pengajian yang dapat merapatkan jurang ketidaksepadanan di antara kehendak industri dan graduan yang dihasilkan oleh politeknik. Kajian ini dijalankan bertujuan untuk penerokaan pengalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The public has voiced concerns regarding the employability of graduates in various related institutions, causing distress among students considering furthering their education to a higher level due to the worrisome state of graduate employability (Ismail & Mohamad, 2021). However, there are strategies, steps, and platforms available to enhance graduate employability at various levels.…”
Section: Issue 3: Universities Implementing Platforms or Launchpads F...mentioning
confidence: 99%
See 1 more Smart Citation
“…The public has voiced concerns regarding the employability of graduates in various related institutions, causing distress among students considering furthering their education to a higher level due to the worrisome state of graduate employability (Ismail & Mohamad, 2021). However, there are strategies, steps, and platforms available to enhance graduate employability at various levels.…”
Section: Issue 3: Universities Implementing Platforms or Launchpads F...mentioning
confidence: 99%
“…Moreover, the issue of graduate employability is not solely attributed to economic stagnation but is also exacerbated by an influx of foreign workers. It is undeniable that Malaysia is seen as a haven for immigrants, particularly those from Indonesia and Thailand, who find employment opportunities easily, particularly in the manufacturing and industrial sectors (Ismail & Mohamad, 2021). These countries have high population densities, leading to limited job opportunities for their citizens.…”
Section: Issue 3: Universities Implementing Platforms or Launchpads F...mentioning
confidence: 99%
“…The results of the research reported by Khazanah Research Institute (2018) found that many diploma graduates expect a salary of RM2,000 per month. Also, Ismail (2012) submits that this starting salary is for new graduates. Other findings from Ang et al (2003) show that foreign workers receive smaller salaries than local salaries even though their workloads are the same, which is at par with the new graduates.…”
Section: Fig 2 -Uthm Graduates Who Earn a Salary Equivalent To Their ...mentioning
confidence: 99%
“…Many improvements ensure that graduates have employability following the desires of employers. Yet, many complaints from employers regarding the weaknesses of graduates' employability (Ismail, 2012). A statistical report from the Department of Statistics Malaysia (2019) found that the number of unemployed graduates in 2018 was 162.0 thousand people, an increase of 4.6 % from 2017 of 154.9 thousand people (Jabatan Perangkaan Malaysia, 2019).…”
mentioning
confidence: 99%
“…The capacity of graduates to communicate vocally and in writing in English is an essential qualification, followed by their ability to think critically. Since today's business community is infinite and endless, managers look for highly qualified employees such as communication, coordination, issue resolution, project and company management, strategy and organisation, self-management and lifetime learning (Ismail, 2012). Next, poor academic performance contributes to graduate students' low marketability.…”
Section: Introductionmentioning
confidence: 99%